The Formation of Kaunas University Library Stock (1923–1950) - Lietuvninkaitė, Nijolė (Knygotyra, 1993)
In this article the analysis of stocking conditions of Kaunas University Library, based on historical and statistical methods, is presented. This library functioned not only as University library – in those times it fulfilled the principle tasks of National Library: 1) formation and storing of the stock of Lithuanian printed publications, 2) formation of the stock of foreign printed publications conforming to the State interests, 3) registration of current and retrospective national bibliography, 4) library service. Kaunas University Library was the largest one in independent Lithuania up to the receiving back of Vilnius Region in 1939. It had universal scientific library stock. The stocking was distinguished by extensive subjects, retrospective volume and accumulation of rare printings. Great importance was attached to the unique collection of Lithuanian printed publications. The volume of the stock grew rapidly. The library accumulated 100000 copies of printings during the first decade of its work. In 1950 it possessed 403839 copies. The main acquisition sources were these: deposit copies of Lithuanian printings, Lithuanian and foreign book-shops, international interlibrary loan, gifts. In 1950, when Kaunas University was closed, the main part of the library stock and premises fell to the share of Kaunas Poly technical Institute. At present more than 200000 copies of Kaunas Uneversity Library’s printings are stored there. The rest part of the stock was transmited to Kaunas Medical Institute, Kaunas Public Library, Vilnius University and Academy of Sciences.